ANALISIS KINERJA APARATUR DESA DALAM PENYELENGGARAAN PEMERINTAHAN DI DESA SENDAWAR KABUPATEN SELUMA - Heliza Soviana (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study aims to analyze the performance of village apparatus in the administration of government in Sendawar Village, Seluma Regency. The data collection technique was through observation, in-depth interviews, and documentation, and involved eight key informants consisting of village heads, village secretaries, village officials, and the community. The results of the study show that in general, the performance of village officials in Sendawar Village still faces various serious obstacles, especially in terms of low productivity and service quality due to the lack of human resource competence, limited understanding of main tasks and functions, and low mastery of information technology such as computers. Although there are village officials who already have higher education, the collective performance is still not optimal, reflected in the slow completion of public administration, low attendance discipline, and lack of clarity in service procedures. From the aspect of responsiveness, the community assesses that village officials tend to be slow to respond to administrative needs such as correspondence and other services. In terms of responsibility, the implementation of duties is not fully in accordance with the principles of good administration, and there are still inconsistencies between policy and implementation. In terms of accountability, community involvement in village deliberations is still minimal and uneven, resulting in a lack of transparency and public participation in village decision-making. These findings show that there is a need for intensive coaching, continuous training of apparatus competencies, and strengthening a digital-based village governance system in order to achieve effective, efficient, and participatory village governance. Keywords: Village Apparatus Performance, Village Government, Productivity, Service Quality, Responsiveness, Accountability